Gendered sweetpotato trait preferences and implications for improved variety acceptance in Uganda - Mulwa, C.K.; Campos, Hugo; Bayiyana, I.; Rajendran, S.; Ssali, R.T.; McEwan, M.; Heck, S. (Wiley, 2024)
The principal selection objective in crop breeding has for a long time been driven by agronomic gains like yield maximization and climate resilience. Nevertheless, the continued low adoption of new varieties and documented gender technology adoption gap has triggered re-thinking of this strategy, with end-user acceptability of released varieties a key strategy in breeding objectives. Using a mixed methods approach with a survey of 122 producers and focus group discussions with 200 male and female producers in two major sweetpotato (Ipomoea batatas (L.) Lam) producing districts in Uganda, this study set out to understand gender-disaggregated traits that drive acceptance for improved sweetpotato varieties, as a guide to development of new varieties in the region. A generalized structural equation modelling (GSEM) approach is used to analyze how interrelated trait preferences shape acceptance for improved varieties, while in-depth insights from a qualitative approach are used to further ground observed results. Traits such as high root yields, drought tolerance, and Vitamin A are shown to be key drivers to acceptance of improved varieties, while good taste and dry matter content dampen acceptance of improved varieties in favor of landraces. Male farmers are also shown to mainly prefer agronomic traits such as high yields and stress tolerance while women mostly prefer quality traits such as good taste, Vitamin A and high dry matter content. To achieve higher acceptability and adoption of improved varieties across the gender divide, new varieties need to not only consider agronomic gains, but also quality-related traits such as taste and dry matter content.